Design and accuracy assessment of a multi-input single Ended Primary Inductor Converter (SEPIC) for highly efficient output from hybrid sources of renewable energy - Rakeen, Sheikh Mustahsin Ahmed; Mahmud, Tahmin; Araf, Afrid Uddin; Ahmed, Nayeem (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.